Association between functional balance and knee extensors strength in people with Parkinson’s disease - Clael, Sacha; de Lima, Filipe Dinato; Brandão, Elaine Cristina da Silva; Rodrigues, Jhonatan Conrado; Marcelino, Camila Wells Damato; Pinheiro, Rafaela do Vale; Neto, José Celi; Bezerra, Lídia Mara Aguiar (PAJAR - Pan-American Journal of Aging Research, 2019)
Aims: The aim of this study is to verify if there is a correlation between functional balance and muscular strength of knee extensors in individuals with Parkinson’s disease. Methods: The sample consisted of 28 volunteers with Parkinson’s disease (age: 65.43±8.48 years, height: 1.68±0.10 cm, weight: 71.50±13.27 kg) classified on the modified Hoehn & Yahr scale. The Four Step Square Test and the isokinetic dynamometer were used to evaluate the dynamic balance and muscular strength of knee extensors, respectively. Results: The peak torque shows a moderate, negative and significant correlation with the Four Step Square Test (right knee: r=-0.471 and p=0.012; left knee: r=-0.444 and p=0.018). Conclusions: There is a negative, moderate and significant association between muscular strength of knee extensors and dynamic balance in Parkinson’s disease individuals. *** Associação entre o equilíbrio funcional e a força dos extensores do joelho em pessoas com a doença de Parkinson *** Objetivos: O objetivo deste estudo é verificar se há correlação entre o equilíbrio funcional e a força muscular de extensores de joelho em indivíduos com doença de Parkinson. Métodos: A amostra consistiu de 28 voluntários com a doença de Parkinson (idade: 65,43±8,48 anos; estatura: 1,68±0,10 cm; peso: 71,50±13,27 kg) classificados na escala de Hoehn & Yahr modificada. O Four Step Square Test e o dinamômetro isocinético foram utilizados para avaliar o equilíbrio dinâmico e a força muscular dos extensores do joelho, respectivamente. Resultados: O pico de torque mostra uma correlação moderada, negativa e significante com Four Step Square Test (joelho direito: r=-0,471 e p=0,012; joelho esquerdo: r=-0,444 e p=0,018). Conclusões: Há uma associação negativa, moderada e significativa entre a força muscular de extensores de joelho e o equilíbrio dinâmico em indivíduos com doença de Parkinson. Palavras-chave: Dinamômetro de Força Muscular; Neurotransmissores; Degeneração Neural; Substância Negra; Atividades Cotidianas.